ArticleEvaluation of Some Methods forPreparing Glipizide-β-Cyclodextrin Inclusion Complexes: Preparing glipizide-β-cyclodextrin inclusion complexes - Vipul P. Patel,; Natvarlal M. Patel, (Iranian Journal of Pharmaceutical Sciences, 2009)
Glipizide has been found to form inclusion complexes with β-cyclodextrin (β-CD) in solution and in solid state. The present study was undertaken to determine a suitable method for scaling up glipizide-β-CD inclusion complex formation and to evaluate the effect of some parameters on the efficiency of complexation. The solid inclusion complexes of glipizide and β-CD were prepared at a molar ratio of 1:1 and 1:2 by mixing, kneading, and co-precipitation methods both on small and large scales. The effect of parameters such as kneading time and temperature on complexation was also studied. Characterization was performed using infrared spectroscopy, X-ray diffractometry, and dissolution studies. In vitrorelease studies were carried out in phosphate buffer (pH 7.4). All the methods of preparation of complexes were found to be useful in increasing the solubility of glipizide except mixing method where the rise in solubility was not significant. Both kneading and co-precipitation methods in 1:2 molar ratios were found to be equally effective inimproving the solubility of glipizide. The formation of inclusion complexes was evident in these formulations as shown by IR and XRD studies. But when carried out on a large scale, co-precipitation method was found to be more tedious and time-consuming than kneading method. Moreover percent recovery of complexes in the kneading method was found to be 98.76% as compared to 92.05% in case of co-precipitation method. Drug content studies, IR spectroscopic studies, X-ray diffractometry studies andin vitrodissolution study data indicated that inclusion complexes prepared by kneading method in 1:2 molar ratios were suitable for improving the solubility of glipizide. The same formulation was prepared at large scale and optimum formulation conditions were established.